Evaluation of anti-acne properties of phloretin in vitro and in vivo - Kum, H.; Roh, K.-B.; Shin, S.; Jung, K.; Park, D.; Jung, E. (International Journal of Cosmetic Science, 2016)
Synopsis Objective This study aimed to investigate the anti‐acne properties of phloretin in vitro and in vivo. Methods Anti‐microbial activity against Propionibacterium acnes (P. acnes), Propionibacterium granulosum (P. granulosum) and Staphylococcus epidermidis (S. epidermidis) were observed by the minimum inhibitory concentration (MIC) and disc diffusion methods. The anti‐inflammatory effects were studied in HaCaT cells based on P. acnes‐induced inflammatory mediators, including PGE2 and COX‐2, examined through enzyme‐linked immunosorbent assay (ELISA) and luciferase reporter gene assay. Thirty healthy subjects with whiteheads participated in the clinical study. Comedo counting, and the amount of sebum and porphyrin were measured before treatment and following 4 consecutive weeks of treatment with phloretin. Results Phloretin showed anti‐microbial activities against P. acnes, P. granulosum, S. epidermidis with the MIC of 0.5, 0.5 and 0.25 mg mL−1, respectively. P. acnes‐induced activation of the COX‐2 promoter was markedly attenuated by phloretin treatment. Consistent with these results, inhibition of PGE2 production was also observed. In 1‐month, placebo‐controlled trials, phloretin showed clinically and statistically significant reduction of comedo counts and sebum output level. Compared to before treatment, whiteheads, blackheads, papules, sebum output level and amount of sebum and porphyrin were significantly decreased at 4 weeks in the test group. Conclusions This study revealed that phloretin inhibits the growth of P. acnes, P. granulosum, and S. epidermidis. In addition, we demonstrated that phloretin attenuates COX‐2 and PGE2 expression during the P. acnes‐induced upregulation of inflammatory signalling. Clinical studies further suggested that treatment with formulations containing phloretin confers anti‐acne benefits. Based on these results, we suggest that phloretin may be introduced as a possible acne‐mitigating agent. Résumé Objectif La présente étude visait à étudier les propriétés anti‐acné de phlorétine in vitro et in vivo. Méthodes L'activité anti‐microbienne contre Propionibacterium acnes (P. acnes), Propionibacterium granulosum (P. granulosum), Staphylococcus epidermidis (S. epidermidis) a été étudiée par la method de concentration minimale inhibitrice (CMI) et par des procédés de diffusion de disque. Les effets anti‐inflammatoires ont été étudiés dans des cellules HaCaT, basés sur l'induction des médiateurs inflammatoires, y compris la PGE2 et de la COX‐2, par P. acnes et examinés par ELISA et par le dosage du gène rapporteur de luciférase. Trente sujets sains avec points blancs ont participé à l’étude clinique. Le comptage des comédonset la quantité de sébum et de la porphyrine ont été mesurés avant traitement et après quatre semaines consécutives de traitement avec la phlorétine. Résultats La phloretin a montré des activités anti‐microbiennes contre P. acnes, P. granulosum, S. epidermidis avec la CMI de 0,5, 0,5, 0,25 mg mL−1, respectivement. L'activation du promoteur de la COX‐2 induite par P. acnes a été sensiblement atténué par le traitement à la phlorétine. Conformément à ces résultats, l'inhibition de la production de PGE2 a également été observée. En un mois, les essais contrôlés par placebo, ont montré pour la phloretine une réduction cliniquement et statistiquement significative du nombre de comédons et du niveau de production de sebum. Par rapport à avant le traitement, les points blancs et noirs, les papules, le niveau de séborrhée, et la quantité de sébum et de porphyrine étaient significativement diminué à 4 semaines dans le groupe test. Conclusions La présente étude a révélé que la phlorétine inhibe la croissance de P. acnes, P. granulosum, et S. epidermidis. De plus, nous avons démontré que la phlorétine atténue l'expresssion de COX‐2 et de PGE2 au cours de l'augmentation de signalisation inflammatoire induite par P. acnes. Des études cliniques ont en outre suggéré que le traitement avec des formulations contenant phloretine confère des avantages anti‐acné. Basé sur ces résultats, nous suggérons que phloretine peut être présenté comme un agent potentiel anti‐acné.